А1) 3*(х+3)-3*(4-х)-х-3 А2) 3*(х+5)-(4-х)-(1+3)*х-3 А3) 2*(х+4)-3*(2-х)-х-4 А4)...

0 голосов
78 просмотров

А1) 3*(х+3)-3*(4-х)-х-3

А2) 3*(х+5)-(4-х)-(1+3)*х-3

А3) 2*(х+4)-3*(2-х)-х-4

А4) х+1-5*(2-х)-(5+1)*Х-5

А5) х+3-(2-х)-х-4

А6) 4*(х+3)-(5-х)-х-4

А7) 3*(х+3)-4(1-х)-(4+3)х-1

А8) 5*(х+5)-3*(3-х)-х-3

А9) 2*(х+2)-5*(2-х)*(5+2)*х-1

А10) 2*(х+4)-4*(5-х)-(4+2)*х-3


Математика (12 баллов) | 78 просмотров
Дан 1 ответ
0 голосов

А1) 3*(х+3)-3*(4-х)-х-3=3x+9-12+3x-x-3=5x-6

А2) 3*(х+5)-(4-х)-(1+3)*х-3=3x+15-4+x-x-3x-3=8

А3) 2*(х+4)-3*(2-х)-х-4=2x+8-6+3x-x-4=4x-2

А4) х+1-5*(2-х)-(5+1)*Х-5=x+1-10+5x-5x-x-5=-14

А5) х+3-(2-х)-х-4=x+3-2+x-x-4=x-3

А6) 4*(х+3)-(5-х)-х-4=4x+12-5+x-x-4=4x+3

А7) 3*(х+3)-4(1-х)-(4+3)х-1=3x+9-4+4x-4x-3x-1=4

А8) 5*(х+5)-3*(3-х)-х-3=5x+25-9+3x-x-3=7x+13

А9) 2*(х+2)-5*(2-х)*(5+2)*х-1=2x+4-10+35x^2-1=35x^2+2x-7

А10) 2*(х+4)-4*(5-х)-(4+2)*х-3=2x+8-20+4x-4x-2x-3=-15

(2.4k баллов)